Taste of Ethnographic Things : the Senses in Anthropology. - Stoller, Paul (Contemporary ethnography., 1989)
Anthropologists who have lost their senses write ethnographies that are often disconnected from the worlds they seek to portray. For most anthropologists, Stoller contends, tasteless theories are more important than the savory sauces of ethnographic life. That they have lost the smells, sounds, and tastes of the places they study is unfortunate for them, for their subjects, and for the discipline itself. The Taste of Ethnographic Things describes how, through long-term participation in the lives of the Songhay of Niger, Stoller eventually came to his senses. Taken together, the separate chapters speak to two important and integrated issues. The first is methodological--all the chapters demonstrate the rewards of long-term study of a culture. The second issue is how he became truer to the Songhay through increased sensual awareness.